What is the way out? : innovations of Haier Group in supply chain finance - Song, Hua, (SAGE Business Cases., 2017)
As Haier Finance Co., Ltd. (Haier Finance) cannot meet the financial demands of many distributors downstream, Haier Group (Haier) seeks to, via its supply-chain finance platform, partner with Ping An Bank and provide supply-chain financial services with collaterals or based on credit. This case studies Haier's supply-chain finance by detailing its background and operational models and analyzing potential risks and challenges, providing reference for traditional manufacturers to transform and upgrade themselves through "Internet Plus" and supply-chain finance.